PDGFA in Cashmere Goat: A Motivation for the Hair Follicle Stem Cells to Activate - Irene Pazzaglia; Francesca Mercati; Marco Antonini; Stefano Capomaccio; Katia Cappelli; Cecilia Dall’Aglio; Antonietta La Terza; Matteo Mozzicafreddo; Cristina Nocelli; Stefano Pallotti; Dario Pediconi; Carlo Renieri (Animals, 2019)
The cashmere hair follicle (HF) perpetually goes through cycles of growth, involution and rest. The photoperiod is the main factor in the control of seasonal coat change in cashmere goats while stem cells play a crucial role in the HF growth. Several factors, including Platelet-Derived Growth Factor A (PDGFA), Bone Morphogenetic Protein 2 (BMP2) and Lim-Homeobox gene 2 (LHX2) are implicated in HF morphogenesis and cycle. In this work, the mentioned molecules were investigated to evaluate their role in follicular cycle activation. The study was performed on skin samples collected at different periods of HF cycle and the molecular expression of PDGFA, BMP2 and LHX2 was evaluated by Real-Time PCR (qPCR) at each time point. Since PDGFA showed the most variation, the goat PDGFA gene was sequenced and the protein localization was investigated by immunohistochemistry together with PDGF receptor α (PDGFRα). PDGFA immunostaining was observed in the basal layer of the HF outer root sheath and the immunoreaction appeared stronger in the regressive HFs compared to those in the anagen phase according to qPCR analysis. PDGFRα was observed in the HF epithelium, proving the effect of PDGFA on the follicular structure. The data obtained suggest that PDGFA and BMP2 are both implicated in HF cycle in goat. In particular, PDGFA secreted by the HF is involved in the anagen activation.